Effective Dark Current Suppression for High-Detectivity Organic Near-Infrared Photodetectors Using a Non-Fullerene Acceptor - Eun, Hyeong Ju; Kye, Hyojin; Kim, Dahee; Jin, In Su; Jung, Jae Woong; Ko, Seo Jin; Heo, Junseok; Kim, Bong Gi; Kim, Jong H. (ACS Applied Materials and Interfaces, 2021)
Near-infrared organic photodetectors (NIR OPDs) have attracted considerable attention because of their inherent advantages such as a tailorable light absorption property, low-cost fabrication, compatibility with flexible substrates, and room-temperature operation. In particular, the development of NIR detection between 900 and 950 nm is crucial for noise-free communication in ambient environments. In this work, we demonstrate high-detectivity NIR OPDs at 900-950 nm by employing a non-fullerene acceptor (ITIC) used with an NIR-absorbing conjugated polymer (PNIR) for bulk heterojunction (BHJ), which significantly suppressed dark current. Systemic characterizations including electrical, structural, and morphological analyses revealed that ITIC effectively reduces charge recombination during the operation of the OPDs under NIR illumination, resulting in a dark current reduction and high detectivity of over 3.2 × 1011 Jones at 900-950 nm. The results presented here demonstrate that utilizing a non-fullerene acceptor for BHJ-type NIR OPDs is evidently a strategic approach for the simultaneous achievement of the low dark current and high-detectivity of NIR OPDs.
Keywords: Bulk heterojunction (BHJ); Charge recombinations; Morphological analysis; Near infrared photodetectors; Organic photodetector; Room-temperature operation; Simultaneous achievement; Strategic approaches; bulk heterojunction; conjugated polymers; dark current; non-fullerene acceptor; organic near-infrared photodetector